Analyzing Cyclops Application Acceptance in Telkomsel Pamasuka using IDT and TAM - Kadir, Muhammad Idham; Tricahyono, Dodie (Jurnal Bisnis dan Pemasaran Digital, 2023)
Purpose: In this thesis, we will examine how much employee acceptance in the Pa Masuka Area, especially “Network” and “Sales', which totals around 522 people to the CYCLOPS application using the Innovation Diffusion Theory (IDT) and Technology Acceptance Model (TAM) methods, then an online survey is conducted. Research Methodology: Data analysis was performed using a Structural Equation Modeling (SEM) model. Results: Digitization of processes at Telkomsel continues to be carried out to increase the effectiveness of employee work, including in the Pausuka Area, especially in the Area Network Operations Sub-Directorate of Pausuka which is responsible for 18,000 sites serving 30 million customers based on April 2023 data.CYCLOPS is a supporting application for digitizing processes that makes it easier for employees, especially the "Network" and "Sales" sections, to observe network conditions (Live Monitoring), find out the potential for network development, make improvements that are right on target according to set priorities to carry out network quality tests. Conclusions: This study concludes that the combined use of Innovation Diffusion Theory (IDT) and the Technology Acceptance Model (TAM) effectively explains the factors influencing the acceptance of the Cyclops in-house application by Telkomsel employees in the Pamasuka area. Unlike consumer technologies like smartwatches or 5G, which require user observation before adoption, in-house applications like Cyclops are often used directly due to internal work demands. Limitations: This research is limited to Telkomsel employees in the Pamasuka area and focuses only on the Cyclops application within sales and network divisions. Future studies can expand to other regions, different departments, or compare multiple in-house applications Contributions: The findings provide valuable insights for companies developing internal applications. To improve adoption, developers should enhance technical features and conduct regular outreach to inform employees about the application's functions and benefits. This could turn observability into a strength, helping employees better understand and utilize internal tools like Cyclops, ultimately increasing productivity and application value.